PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS PERMAINAN TRADISIONAL RAKYAT DAERAH RIAUUNTUK KELAS IV SD - Edwar, Suci Nitia; Roza, Yenita; Sakur, Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The purpose of this research is to develop mathematical learning materials based on traditional folk games for grade 4th of elementary school in Riau. Mathematics was known as a difficult subject that made many student did not interested in learning them. This perception also happen because of the abstract nature of mathematics it self. Variations of innovative teaching need to be done to attract students to fully participatein mathematics learning process. Good and attractive instructional can be seen from various aspects, including the aspects of the language that is easy to understand by the students, support of an interesting picture according to the learning material. This Research use Research and Development (R & D method). Development model used in this study is a model of Plomp that consists of four phases, namely: (1)Initial Research, (2)Design, (3) The realization phase, (4)Testing, evaluation and revision. Based on the results of the data analysis and discussion, it can be concluded that the teaching material is valid with an average rating of 3,36 and has the practicality to be used in 4th grade of elementary school with score reached 90%. This learning material is recomended to use for mathematics class at 4th grade of elementary schools especially in Riau.Keywords: Mathematics teaching material for fourth grade, traditional folk games of Riau,